2018
DOI: 10.1186/s13028-018-0424-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological assessment of the risk of canine mast cell tumours based on the Kiupel two-grade malignancy classification

Abstract: BackgroundThe degree of differentiation of mast cell tumours (MCTs) is the most important feature and reflects the morphological characteristics and metastatic potential of the tumour and its likely response to treatment and the prognosis. The aim of this study was to epidemiologically analyse the risk of MCT development in dogs according to breed, age, sex, size and anatomical location of the tumour using the Kiupel grading system. The analysis involved 492 dogs selected based on a histopathological assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 40 publications
(69 reference statements)
5
32
0
3
Order By: Relevance
“…8 and in median survival times. 29,31 Nonetheless, TT did deliver clinical benefit to 4 dogs in the study with high-grade MCT with enlarged locoregional LNs where metastasis was not confirmed on FNAs.…”
Section: Discussionmentioning
confidence: 89%
“…8 and in median survival times. 29,31 Nonetheless, TT did deliver clinical benefit to 4 dogs in the study with high-grade MCT with enlarged locoregional LNs where metastasis was not confirmed on FNAs.…”
Section: Discussionmentioning
confidence: 89%
“…The median age was 8.5 years, all the patients had been neutered and there was an even distribution of gender. There was an overrepresentation of medium to large dogs with Staffordshire Bull Terriers featuring prominently (46)(47)(48)(49). The number of patients in this study was limited by its retrospective nature, and the small sample size was too low for any definitive statistical analysis.…”
Section: Discussionmentioning
confidence: 93%
“…Śmiech et al . [ 20 ] classified 75.8% of MCTs as low intensity and 24.2% as high intensity. These results were similar to those of Hergt et al .…”
Section: Discussionmentioning
confidence: 99%
“…According to the Kiupel system, 56.17% (17/30) of samples were of low intensity and 43.33% (13/30) were of high intensity. Śmiech et al [20] classified 75.8% of MCTs as low intensity and 24.2% as high intensity. These results were similar to those of Hergt et al [21] who classified 74.46% of MCTs as low intensity and 25.54% as high intensity.…”
Section: Discussionmentioning
confidence: 99%